Suffixes in Business Documents of Utraco Company: a Morphological Analysis - Hendra Nugraha (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2017)
This final report explained about Suffixes in Business Documents Quality Manual 2007 and Manual Record Procedure 2013 of Utraco Company: Morphological Analysis. This research aims to know about suffix specific and also suffix most frequent in business document Quality Manual and Audit Report. In this research the writer used morphology theory are written by Aronof and Fudemen(2005), and Yule (2010). This research used descriptive qualitative. The writer also used dictionary to find out that changed the word class attached by suffix. Based on the analysis that has been done, suffix can change word class, one-word class to the other word class. The writer found 152 suffix in business document, kinds of suffix are –ary, -ance, -er, -ful, -ion, -ive, -ity, -ly, -ment, -ness, and –or. This suffix can change word class that are, verb to noun, adjective to adverb, adjective to noun, and noun to adjective, and verb to noun is most frequent in business document there are 45, suffix –ion is most frequent in business document there are 28, as conclusion word class verb to noun is the most frequent, suffix occurred in business document of Quality Manual and Audit Report with suffix –ion 28 occurrences.